Employment opportunities in the social economy within the framework of the forestry strategy to combat climate change - Díaz Martínez, Elena; Martínez-Alcalá, Isabel María; Meseguer Sánchez, J.Victor (Cooperativismo & Desarrollo, 2025)
Forestry strategies are being revised in light of the impacts of climate change: rising temperatures, prolonged droughts, pest proliferation, and an increased risk of devastating fires. Added to this is the limited planning capacity and resources of public administrations to manage the extensive forest area, both public and private. In this context, the social economy is emerging as an effective model of cooperation for optimising public spending and promoting sustainable forest management. Its principles enable the transfer of carbon capture technologies from universities to social enterprises, as well as the training of workers in traditional forestry tasks aimed at mitigating and offsetting emissions in regulated markets. It also proposes strengthening coordination among environmental, agricultural, and forestry policies through public procurement reserved for social-economy entities, in accordance with European guidelines and the Sustainable Development Goals of the 2030 Agenda. This study, focused on the Region of Murcia but with extrapolable results, adopts a qualitative approach based on documentary analysis and expert interviews to propose a paradigm shift that recognises forests as essential ecosystem services for climate regulation and the use of forest biomass as a renewable energy source that contributes to forest resilience.